Pitcher reaction time in slow pitch softball - Lyu, B.; Smith, L.; Smith, N. (Sports Engineering, 2025)
Pitchers need to react quickly to avoid being hit by a batted ball. While reaction time has been studied extensively in controlled laboratory conditions, it has not been measured for pitchers in play under conditions of intermittent risk and game distractions. This study used EMG (electromyography) and high-speed video to measure the available response time and reaction time of softball pitchers to batted balls during play. Data was collected from nine slow-pitch softball tournaments, comprising 84 out of 304 recorded events where a ball was hit back toward the pitcher. The mean reaction time of softball pitchers to batted balls was 0.202 s, while the available response time was 0.454 s. The study found no statistical difference between the reaction time of amateur and professional athletes, while the reaction of both groups decreased with increasing threat level. The study found that movement time was highly correlated with the success of a pitcher defensive movement.